Influence of curve morphology and location on the efficacy of rigid conservative treatment in patients with adolescent idiopathic scoliosis. (1st February 2021) - Strube, Patrick; Gunold, Maria; Müller, Tanja; Leimert, Mario; Sachse, André; Pumberger, Matthias; Putzier, Michael; Zippelius, Timo
Abstract : Aims: The aim of the present study was to answer the question whether curve morphology and location have an influence on rigid conservative treatment in patients with adolescent idiopathic scoliosis (AIS). Methods: We retrospectively analyzed AIS in 127 patients with single and double curves who had been treated with a Chêneau brace and physiotherapeutic specific exercises (B-PSE). The inclusion criteria were the presence of structural major curves ≥ 20° and < 50° (Risser stage 0 to 2) at the time when B-PSE was initiated. The patients were divided into two groups according to the outcome of treatment: failure (curve progression to ≥ 45° or surgery) and success (curve progression < 45° and no surgery). The main curve type (MCT), curve magnitude, and length (overall, above and below the apex), apical rotation, initial curve correction, flexibility, and derotation by the brace were compared between the two groups. Results: In univariate analysis treatment failure depended significantly on: 1) MCT (p = 0.008); 2) the apical rotation of the major curve before (p = 0.007) and during brace treatment (p < 0.001); 3) the initial and in-brace Cobb angles of the major (p = 0.001 and p < 0.001, respectively) and minor curves (p = 0.015 and p = 0.002); 4) major curve flexibility (p = 0.005) and the in-brace curve correction rates (major p = 0.008, minor p = 0.034); and 5) the length of the major curve (LoC) above (p < 0.001) and below (p = 0.002) the apex. Furthermore, MCT (p = 0.043, p = 0.129, and p = 0.017 in MCT comparisons), LoC (upper length p = 0.003, lower length p = 0.005), and in-brace Cobb angles (major p = 0.002, minor p = 0.027) were significant in binary logistic regression analysis. Conclusion: Curve size, location, and morphology were found to influence the outcome of rigid conservative treatment of AIS. These findings may improve future brace design and patient selection for conservative treatment. Cite this article: Bone Joint J 2021;103-B(2):373–381.